(untitled) (مجلة الواحات للبحوث والدراسات, 2020)
As Is Known, The Original Is To Give Fatwa Only With Approved Statements – Most Correct And Famous. Due To The Change In People’s Customs, Habits, Difference In Their Environment, Time And The Necessities, This Research Was Conducted To Examine The Question Of The Possibility Of Issuing Fatwas With Weak Statements If They Are Achieved In The Interests Of The People In The Framework Of The Maliki School. The Result Is The Permission With Specific Requirement, With Its Application. Keywords- The Fatwa.1 The Weak Statement. 2 The Maliki School